Somatic cell counts in refrigerated raw milk from individual producers through rapid methods (Research, Society and Development, 2021)
Objectives: The evaluated the effect of rapid methods for somatic cell count (SCC) in milk. We collected 140 milk samples from dairy cows originating from 20 producers located in the state of Piauí. The design was adopted in a randomized block design with two treatments T1 and T2 and seven replicates analyzed in duplicate. The average of the treatments (T1) somaticell and (T2) ekomilk scan were respectively 432.56 and 229.22. Kits somatcell and ekomilk scan used in this study were effective for CCS count in refrigerated raw milk from individual producers.